Perancangan Website UMKM BB Bakery Menggunakan Visual Studio Code - Ainahaq Luisa Fauziah; Desriany Rahmadilla; Fatihatul Jannah (CV. ITTC INDONESIA, 2024)
This article aims to design a website for Roti BB Bakery MSMEs using Visual Studio Code as a tool to improve marketing and promotion of bread products. The method used includes data collection through interviews with the owner and direct observation at the bakery, followed by designing the database, display, and website structure. The result of this implementation is a website https://bbbakery.github.io/bbbakery/. From results of this design show that the developed website functions as an effective digital storefront, provides complete information about products, and facilitates interaction with consumers. The conclusion of this project states that the implementation of this website is expected to increase the existence of Roti BB Bakery in the digital market, expand consumer reach, and support business sustainability.